Snapshot of current carotid artery stenting practice and accreditation in the USA. Issue 4 (5th October 2019) - Sacks, David; Farrell, Mary Beth; Katzen, Barry T; Lally, Mary; Matsumura, Jon S; Merrill, Nancy
Abstract : Objective: The aim of this exploratory study was to compare the performance of carotid artery stenting (CAS) best practices between Intersocietal Accreditation Commission (IAC) accredited facilities and non-accredited facilities certified by the Centers for Medicare and Medicaid Services (CMS). Methods: A random, anonymous survey was sent to CMS and IAC accredited facilities querying facility routine performance of 16 CAS procedure components found in published guidelines and utilised during clinical trials. Results: There were 28 responses (response rate=17%). Significant differences were found between the CMS and the IAC facilities for four of 16 procedure measures: determination of modified Rankin Scale score prior to stenting (p=0.012, 95% CI 20% to 80%), accurate measurement of per cent stenosis using electronic callipers (p=0.005, 95% CI 24% to 84%), confirmation of anticoagulation with activated clotting time greater than 250 s prior to crossing the lesion (p=0.03, 95% CI 7% to 69%), and comparison of facility outcomes to accepted benchmarks for stroke and death (p=0.03, 95% CI 7% to 69%). Overall, IAC facilities performed all 16 procedures more frequently (97%) than CMS facilities (66%) (p<0.001, 95% CI 24% to 36%). Conclusions: Although the sample size was small, the results demonstrated IAC accredited facilities are more likely to follow best practices, to use quantitative tools to select appropriate patients, and quantitively measure patient-centred clinical outcomes compared with CMS certified facilities. The findings raise the question as to the value of CMS certification versus IAC accreditation as a requirement for reimbursement.